Unilateral Tuberothalamic Artery Ischemia Caused by Pituitary Apoplexy - Bettag, Christoph; Strasilla, Christoph; Steinbrecher, Andreas; Gerlach, Rüdiger (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Importance Pituitary apoplexy (PA) occasionally occurs in patients with pituitary adenoma and may cause severe functional deficits. Headache, pituitary insufficiency, visual impairment, and cranial nerve palsies are the most frequent symptoms in patients with PA. Secondary cerebral ischemia develops in only a limited number of PA patients. Two pathogenic mechanisms were previously proposed. One states that ischemia may be due to major vessel encasement or to vessel compression, as a result of extended tumor growth. The second states that cerebral vasospasm following PA may cause ischemia. We present another mechanism. After PA, a sudden increase in suprasellar tumor volume can lead to compression of perforating arteries causing hypoperfusion and subsequent focal ischemia of the thalamus, basal ganglia, and internal capsule.Clinical Presentation We present the case of a 75-year-old woman who, after having PA, developed cerebral ischemia in the territory of the left anterior thalamus and internal capsule that is primarily supplied by the tuberothalamic artery. Computed tomography and magnetic resonance imaging are used to describe how mechanical compression of the tuberothalamic artery caused this rare phenomenon. The recent literature, vascular anatomy, and pathophysiologic aspects of PA are discussed.Conclusion PA can lead to compression of perforating arteries, for example, the tuberothalamic artery supplying the thalamus or lenticulostriate region, and thus cause hypoperfusion and subsequent focal cerebral ischemia. This may occur when perforating cerebral arteries are affected and compressed by the sudden increase in tumor volume due to hemorrhage or tumor swelling.
Keywords: pituitary apoplexy; cerebral ischemia; thalamus